Advances in Human Dendritic Cell-Based Immunotherapy Against Gastrointestinal Cancer - Ni, Ling (Frontiers in Immunology, 2022)
Dendritic cells (DCs), the strongest antigen-presenting cells, are a focus for orchestrating the immune system in the fight against cancer. Basic scientific investigations elucidating the cellular biology of the DCs have resulted in new strategies in this fight, including cancer vaccinology, combination therapy, and adoptive cellular therapy. Although immunotherapy is currently becoming an unprecedented bench-to-bedside success, the overall response rate to the current immunotherapy in patients with gastrointestinal (GI) cancers is pretty low. Here, we have carried out a literature search of the studies of DCs in the treatment of GI cancer patients. We provide the advances in DC-based immunotherapy and highlight the clinical trials that indicate the therapeutic efficacies and toxicities related with each vaccine. Moreover, we also offer the yet-to-be-addressed questions about DC-based immunotherapy. This study focuses predominantly on the data derived from human studies to help understand the involvement of DCs in patients with GI cancers.